Peningkatan Efisiensi Air melalui Penerapan Sistem Irigasi Tetes Berbasis Gravitasi dalam Pengelolaan Kebun Alpukat di Pondok Modern Darussalam Gontor - Agung Dwicahyo; Hendri Setiyo Wibowo; Ussisa Ala Taqwa; Muhammad Galang Fachrezy; Muhammad Habibi Albana; Yogi Banar Sasongko; Ahmad Iqbal; Riza Ashari (Abdimas Indonesian Journal, 2025)
This community service program aims to improve the efficiency of avocado garden management at Pondok Modern Darussalam Gontor through the implementation of an appropriate gravity-based drip irrigation system. The main problems faced are uneven water supply due to manual watering, low water use efficiency, and lack of skills of students in the application of irrigation technology. Service activities include designing a simple irrigation system, technical training for students and garden managers attended by 8 staff, preparation of irrigation schedules, and the implementation of a monitoring and routine maintenance system. The results of the activity showed an increase in the efficiency of water distribution, an increase in the competence of students and staff in the installation and maintenance of the drip irrigation system, and the development of an independent learning model that is in line with the vision of the Islamic boarding school. The program also produces complete documentation as a replication guide for other institutions that have similar characteristics.